Destiny Of Love Of Tyler Hawkins In Allen Coulter'sRemember Me Movie (2010): A Psychoanalytic Approach - Nurhayati, Nike; , Drs. Abdillah Nugroho, M. Hum; , Titis Setyabudi, S.S., M.Hum (2013)
This study is aimed to show destiny of love a young rebellious man who ended to death in Allen Coulter's Remember Me movie by using psychoanalytic approach. It is done by establishing two objectives: the first is analyzing the movie based on structural elements of the movie and the second is analyzing the movie based on the psychoanalytic approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Remember Me movie directed by Allen Coulter released in 2010. While the secondary data sources are other materials taken from books, encyclopedia, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. Firstly, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise-en scene, cinematography, sound and editing are related to each other and form the unity into good quality movie, secondly, based on the psychoanalytic analysis, there is a close relationship between the movie story and the reality condition of young man who falls in love. It is reflected by the characters in the movie.